Citizen and self in ancient Greece : individuals performing justice and the law - Farenga, Vincent, 1947- (Cambridge University Press, 2006)
This study examines how the ancient Greeks decided questions of justice as a key to understanding the intersection of our moral and political lives. Combining contemporary political philosophy with historical, literary, and philosophical texts, it examines a series of remarkable individuals who performed 'scripts' of justice in early Iron Age, archaic, and classical Greece. From the earlier periods, these include Homer's Achilles and Odysseus as heroic individuals who are also prototypical citizens, and Solon the lawgiver, writing the scripts of statute law and the jury trial. In democratic Athens, the focus turns to dialogues between a citizen's moral autonomy and political obligation in Aeschyleon tragedy, Pericles' citizenship paradigm, Antiphon's sophistic thought and forensic oratory, the political leadership of Alcibiades, and Socrates' moral individualism.